Coral larval recruitment in north-western Australia predicted by regional and local conditions. (June 2021) - Thomson, Damian P.; Babcock, Russell C.; Evans, Richard D.; Feng, Ming; Moustaka, Molly; Orr, Melanie; Slawinski, Dirk; Wilson, Shaun K.; Hoey, Andrew S.
Abstract: Understanding ecological processes that shape contemporary and future communities facilitates knowledge-based environmental management. In marine ecosystems, one of the most important processes is the supply of new recruits into a population. Here, we investigated spatiotemporal variability in coral recruitment at 15 reefs throughout the Dampier Archipelago, north-western Australia between 2015 and 2017 and identified the best environmental predictors for coral recruitment patterns over this period. Large differences in recruitment were observed among years with the average density of recruits increasing by 375% from 0.017 recruits cm −2 in 2015 to 0.059 recruits cm −2 in 2017. Despite differences in recruitment among years, the rank order of coral recruit density among reefs remained similar among years, suggesting that spatial variation in recruitment within the Dampier Archipelago is partly deterministic and predictable. The density of coral recruits was best explained by percent cover of live corals at both local (within 5 m) and meso-scales (within 15 km), water turbidity and an oceanographic model that predicted larval dispersal. The highest density of coral recruits ( 0.13 recruits cm −2 or 37 recruits per tile) occurred on reefs within sub-regions (15 km) with greater than 35% coral cover, low to moderate turbidity (KD490 < 0.2) and moderate to high modelled predictions of larval dispersal. Our results demonstrate that broad-scale larval dispersal models, when combined with local metrics of percent hard coral cover and water turbidity, can reliably predict the relative abundance of coral recruits over large geographical areas and thus can identify hotspots of recruit abundance and potential recovery following environmental disturbances; information that is essential for effective management of coral reefs. Highlights: Variability in coral recruitment was recorded over 3 years in the Dampier Archipelago. Reefs with consistently high (i.e. hotspots) or low rates of recruitment were identified. Recruitment of spawners was best explained by regional coral cover (15 km). Recruitment of brooders was best explained by local coral cover (5 m). Recruitment models should incorporate metrics such as percent coral cover to improve predictive ability.